Composite peek/carbon fiber pre-shaped rods and sublaminar bands for posterior stabilization of cervico-thoracic junction: A novel technique. (February 2020) - Pipola, Valerio; Boriani, Stefano; Ghermandi, Riccardo; Tedesco, Giuseppe; Evangelisti, Gisberto; Girolami, Marco; Ricci, Alessandro; Gasbarrini, Alessandro
Highlights: Surgery plus radiotherapy is a treatment option when a wide margin is not feasible. Carbon fiber instrumentation improves efficacy of particle radiotherapy. Cervical fixation with carbon fiber rods anchored with sublaminar bands alone. Abstract: The combination of surgery plus radiotherapy is a valid treatment option when en bloc resection with wide margins is not feasible. The aim of this paper is to show a novel technique for fixation of cervico-thoracic junction with carbon fiber reinforced peek pre-shaped rods with sublaminar bands in order to guarantee cervical spine stability and particle therapy efficacy. A 42 years-old man with a Sclerosing Epithelioid Fibrosarcoma (SEF) arising from C7, involving the right latero-cervical region from C5 to the apex of the right lung, underwent an en bloc resection with a double approach (anterior plus posterior). Fixation of cervical spine was achieved with composite PEEK/carbon fiber rods connected to C4 and T2 laminae with sublaminar bands. After surgery, the patient received 9 cycles of chemotherapy (cisplatin, etoposide and adriamycin) and proton therapy. At 2 years follow-up, no local recurrence was detected with implant stability demonstrating no mechanical failure. The main issues related to this case were: planning en bloc resection able to achieve an Enneking appropriate margin; incorporate in the decision making process the functional loss related to the sacrifice of neurological structures infiltrated by the tumor; establish a therapeutic strategy that included, in addition to surgery, adjuvant chemotherapy and radiotherapy for improving local and systemic control; stabilize with implants that do not interfere with accelerated particle radiotherapy.